2012
DOI: 10.1002/ir.20020
|View full text |Cite
|
Sign up to set email alerts
|

International Faculty in American Universities: Experiences of Academic Life, Productivity, and Career Mobility

Abstract: The increasing presence of international faculty members is validated using multiple data sources, and their professional experience is examined in terms of the perception of academic life, productivity, and career mobility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 21 publications
2
55
0
Order By: Relevance
“…Empirical studies have shown that one of the serious influences of burnout is turnover intentions (Jourdain & Chênevert, ; H. Kim & Stoner, ). Faculty turnover often results in substantial economic loss for their academic institutions (D. Kim, Twombly, & Wolf‐Wendel, ) because of the high costs associated with hiring replacements (Johnsrud & Rosser, ; D. Kim et al, ). Moreover, faculty turnover results in indirect or hidden costs, which are often difficult to quantify but are known to be much greater than direct costs (Schloss, Flanagan, Culler, & Wright, ).…”
Section: Faculty Burnout and Turnovermentioning
confidence: 99%
“…Empirical studies have shown that one of the serious influences of burnout is turnover intentions (Jourdain & Chênevert, ; H. Kim & Stoner, ). Faculty turnover often results in substantial economic loss for their academic institutions (D. Kim, Twombly, & Wolf‐Wendel, ) because of the high costs associated with hiring replacements (Johnsrud & Rosser, ; D. Kim et al, ). Moreover, faculty turnover results in indirect or hidden costs, which are often difficult to quantify but are known to be much greater than direct costs (Schloss, Flanagan, Culler, & Wright, ).…”
Section: Faculty Burnout and Turnovermentioning
confidence: 99%
“…Further to national policy, institutional contexts and post‐PhD career decisions, Kim et al . () considered the Collaborative on Academic Careers in Higher Education (COACHE) survey data regarding pre‐tenure international faculty members’ experiences. They found that foreign‐born faculty were more satisfied than those who were US citizens with the tenure process and research and funding expectations, but less satisfied with their sense of fit with departmental and institutional colleagues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings from their research indicated tremendous inequality in the working conditions of study participants, and also revealed how the transient nature of this form of employment encourages questions about not only who gets to move, but from where and to where. Further to national policy, institutional contexts and post-PhD career decisions, Kim et al (2012) considered the Collaborative on Academic Careers in Higher Education (COACHE) survey data regarding pretenure international faculty members' experiences. They found that foreign-born faculty were more satisfied than those who were US citizens with the tenure process and research and funding expectations, but less satisfied with their sense of fit with departmental and institutional colleagues.…”
Section: Academic Mobility Between Two Early Career Scholarsmentioning
confidence: 99%
“…Neoliberal universities recruit international scholars for their cheap labor and high productivity (Mamiseishvili and Rosser 2010;Kim, Twombly, and Wolf-Wendel 2012), all the while presuming their cultural inferiority. The status of a "non-native speaker" serves as a convenient marker of this "inferiority" despite one's actual level of fluency.…”
Section: Feminist Teachers In the Marginsmentioning
confidence: 99%